Pharmacognostic and acute toxicity study of the rhizome of Nymphae lotus L. (Nymphaeaceae) - Muhammad Murtala, Namadina; Aliyu, Nuhu; Sidi, Aliyu Bala; Muhammad Sulaiman, Hafizu; Tahir, Ahmad Abdulkadir; Muhammad Auta, Aminu; Isah, Muhammad Maryam; Ali, Sani; Alhaji, Shehu Shafiu (Asian Journal of Medical and Biological Research, 2019)
Nymphaea lotus belongs to the family Nymphaeaceae and traditionally used in the treatment of aphrodisiac, anodyne, astringent, cardiotonic, sedative, demulcent, analgesic and as anti-inflammatory agent. The objective of the study was to evaluate the phytochemical, physicochemical analysis and safety margin of N. lotus rhizome with the hope of assisting in its standardization for quality, purity and safety. The powdered sample of the rhizome was extracted with aqueous and methanol and evaluated for physicochemical parameters of the plant. The extracts were subjected to qualitative and quantitative phytochemical analysis and acute toxicity study. The physicochemical parameters evaluated include: moisture content (7.4%), total ash (10.3%), water soluble (7.1%), acid insoluble (2.8%), ethanol extractive value (16.7%), and water extractive value (22.0%). The quantitative phytochemical analysis revealed that alkaloids (166.0 mg/g) was the highest phytochemical detected in the rhizome while the lowest was saponins (22.0 mg/g). LD50 of both extracts was above 5000 mg/kg and did not cause mortality in all the tested rats. The results of this finding may be useful in laying down standards and for the compilation of a suitable pharmacopoeia parameters on N. lotus. Asian J. Med. Biol. Res. June 2019, 5(2): 138-145